Pharmacokinetic study of Strongylocentrotus nudus egg polysaccharide in rats and beagles using a 3H-labeling method - Xing, Han; Zhu, Xiaojie; Liao, Jianmin; Kong, Ying; Lu, Yayuan; Zhao, Di; Li, Ning; Chen, Xijing; Qin, Zhiying (Frontiers in Pharmacology, 2023)
Strongylocentrotus nudus egg polysaccharide (SEP) extracted from sea urchins has potential anticancer activity. However, little is known about its pharmacokinetic properties. To investigate the pharmacokinetics of SEP, it was radiolabeled with tritium. Furthermore, a sensitive, selective, and rapid liquid scintillation counter (LSC) method for quantifying 3H-SEP in biological matrix was validated. The lower quantification limit of the method was 4 Bq. The relative standard deviations (RSDs) of the intra- and inter-day precision were <3.0% and <3.9%, respectively. 3H-SEP was successfully applied to investigate the pharmacokinetics of SEP after intravenous administration of 20, 40, and 80 mg/kg (40 μCi/kg) in rats and 5, 10, and 20 mg/kg (6 μCi/kg) in beagles. The AUC(0-t) of SEP at three different doses was 487.81 ± 39.99 mg/L*h, 1,003.10 ± 95.94 mg/L*h, and 2,188.84 ± 137.73 mg/L*h in rats and 144.12 ± 3.78 mg/L*h, 322.62 ± 28.03 mg/L*h, and 754.17 ± 37.79 mg/L*h in beagles. The terminal elimination half-life (t1/2) of SEP was longer in beagles (204.29 ± 139.34 h) than in rats (35.48 ± 6.04 h). The concentration of SEP in plasma declined rapidly in both rats and beagles. All the study results provide detailed pharmacokinetic profiles of SEP in two kinds of animals, which will be helpful for further development.